KIT-13, a novel plasmalogen derivative, attenuates neuroinflammation and amplifies cognition - Hossain, Md Shamim; Mawatari, Shiro; Honsho, Masanori; Okauchi, Tatsuo; Fujino, Takehiko (Frontiers in Cell and Developmental Biology, 2024)
Plasmalogens (Pls) are specialized phospholipids integral to brain health, whose decline due to aging and stress contributes to cognitive impairment and neuroinflammation. This study explores the potential of a novel Pls derivative, KIT-13 (1-O-octadecyl-2-arachidonoyl-sn-glycerol-3-phosphoethanolamine), in mitigating neuroinflammation and enhancing cognition. When administered to mice, KIT-13 exhibited potent memory enhancement attributed to upregulated brain-derived neurotrophic factor (BDNF), a key player in cognitive processes. In vitro experiments with neuronal cells revealed KIT-13’s ability to induce robust cellular signaling, surpassing natural plasmalogens. KIT-13 also promoted neurogenesis and inhibited apoptosis of neuronal-like cells, highlighting its potential in fostering neuronal growth and plasticity. Additionally, KIT-13 treatments reduced pro-inflammatory cytokine expression and attenuated glial activation in the brain. KIT-13’s superior efficacy over natural Pls positions it as a promising therapeutic candidate for neurodegenerative conditions such as Alzheimer’s disease, characterized by cognitive decline and neuroinflammation. This study presents KIT-13 as an innovative approach for addressing cognitive impairment and neuroinflammatory pathologies.